Study of implant Stability in Conjunction with Autogenous Bone Grafts Taken from the Chin by Trephine Burs: "A Clinical and Radiographic Study" - أسعد منذر; عبد العال يحيى (Latakia University Journal -Medical Sciences Series, 2021)
This study was designed to evaluate the results of the stability of dental implants in conjunction with autogenous bone grafts taken from the chin by the trephine burs. The aim of the research is to evaluate the success and stability of dental implants in conjunction with autogenous bone grafts taken from the chin. The sample included 20 implants in conjunction with autogenous bone ring graft for 12 patients who attended oral maxillofacial surgery department in Tishreen University Hospital. The dental implantation was performed in conjunction with autogenous bone ring graft taken from the chin by trephine burs. The stability parameter was evaluated by the ostell device in two time periods (the first during surgery and the second after six months of surgery). The average stability increased after 6 months during follow-up in the upper jaw by 14.53%, in the lower jaw by 10.39%, and in the total sample by 11.84%. For the upper jaw, the average of ISQ value was = 67.88 ± 1.65 during the dental implantation, and the average of ISQ value after 6 months became = 77.74 ± 1.55 and for the lower jaw the average of ISQ value was = 69.40 ± 1.26 during the dental implantation and it became the average ISQ value after 6 months = 80.70 ± 1.26. Conclusion: The stability of the dental implants in conjunction with the autogenous bone grafts taken from the chin showed a good increase, indicating the success of this method.